The Role of a Regional Power in Regional Integration: The case of Nigeria in the Economic Community of West African States - Vushemasimba, Tsungai Melissa (Department of Political Studies, 2023)
Theoretically, it has been determined that the presence of a powerful state within a particular region is a significant ingredient for regional stability and integration. Practically, however, evidence has surfaced that regional powers can equally undermine regional integration. Regional powers bear the greatest financial and operational burdens relating to regional projects and provide relevant leadership. Nigeria has been no exception in ECOWAS; it has made tremendous contributions to regional development – from the establishment of the ECOWAS to the running of its peacekeeping operations (PKOs). Nigeria's efforts in ECOWAS have demonstrated the potency and benefaction of a regional power to the development and stability of a region. This dissertation contributes to a deeper understanding of how leadership can be a method of overcoming Africa's stability challenges through regional integration. The study used Nigeria's role in ECOWAS as the central focus, concentrating on Abuja's contribution to peacekeeping operations in the region, and the impact of this contribution to regional stability. However, an acknowledgement that ECOWAS has not fully realised economic integration largely because of a lack of peace, security, and a stable political environment, is noted. Discussions on ‘economic contributions' relates to Nigeria's provision of financial and logistical support in the region. Finally, the dissertation notes the extent to which a regional power undermines regional integration.